2021
DOI: 10.1097/nnr.0000000000000542
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Self-Monitoring of Blood Glucose in Patients With Type 2 Diabetes

Abstract: The benefit of self-monitoring of blood glucose (SMBG) in the reduction of HbA1c in non-insulintreated participants remains unclear. HbA1c may be improved in this population with SMBG. We aimed to investigate this. Materials and methodsMeta-analyses of randomized controlled trials (RCTs) were performed comparing SMBG versus usual care and structured versus unstructured SMBG; the effect of clinician therapy adjustment based on SMBG readings was examined. Medline, Embase and Cochrane Central were electronically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…The latter is consistent with the findings of two prior metaanalyses, which identified greater clinical benefit when SMBG was followed by responsive treatment modifications (29,30). However, this was not observed in the current study likely due to the broader inclusion criteria.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The latter is consistent with the findings of two prior metaanalyses, which identified greater clinical benefit when SMBG was followed by responsive treatment modifications (29,30). However, this was not observed in the current study likely due to the broader inclusion criteria.…”
Section: Discussionsupporting
confidence: 92%
“…when HbA1c is above target or treatment modification is required ( 15 , 25 ),. Such targeted use of sSMBG may be both clinically- and cost-effective ( 21 , 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Public health messaging for patients and providers can encourage routine care, use of telehealth, and strategies such as self-measured blood pressure monitoring and home blood glucose measurements with clinical support. 15,16 Future work can examine whether chronic disease control status is associated with COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of blood glucose monitoring are important information for physicians to provide appropriate treatment regimens with tailored lifestyle advice to achieve glycaemic control and prevent disease progression [ 5 , 6 , 7 ]. A large body of evidence has accumulated over the years documenting that regular follow-up care [ 8 , 9 ] and structured monitoring of blood glucose [ 10 , 11 ] could significantly prevent the deterioration in glycaemic status. However, previous investigations showed that more than two-fifth of patients with T2DM failed to achieve follow-up attendance at least once per quarter at community health centres [ 12 ], and that only less than one-fifth of T2DM patients were able to perform blood glucose monitoring on a regular basis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%